A Comprehensive Review and Adequacy Evaluation of Voltage Stability Indices for Modern Distribution Systems - Eminoglu, Ulas; Hocaoglu, M. Hakan; Ayasun, Saffet (Praise Worthy Prize Srl, 2010)
It is well known that the network variables and parameters contain sufficient information to obtain the most sensitive bus or line to the voltage collapse in power systems. Accordingly, there has been several static voltage stability indices developed for identifying the buses or lines on the verge of voltage collapse in the literature. In this paper, various voltage stability indices including those originally developed for transmission systems are first reviewed. Then, their adequacies are quantitatively evaluated on a modern distribution test system which has voltage controlled bus (PV-bus). From analyses, it is observed that most of the existing voltage stability indices would be inadequate for assessing the most sensitive bus or line on the verge of voltage collapse in such modern distribution systems. Copyright (c) 2010 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Critical Bus; Modern Distribution Networks; Voltage Stability Indices; Voltage Collapse